Assembly-induced microwave band resonance in gold nanoparticles-based ultrathin and flexible spoof localized surface plasmon. (June 2021) - Wang, Peng; Shen, Xiaopeng; Zhang, Haochi; Xu, Ou; He, Peihang; Wang, Haoshen; Ma, Siyu; Guo, Zhaobin; Jiang, Qing; Gu, Ning; Sun, Jianfei
Abstract: Spoof LSP (Localized Surface Plasmon) is a great advance in metamaterials, expanding the LSP resonance from optical band into microwave band. It will yield amazing outcomes by integration with flexible electronics, wearable electronics and nanophotonics. Here, an ultrathin and flexible spoof LSP prepeared by layer-by-layer (LBL) assembly of gold nanoparticles was demonstrated. The LSPR effects in microwave band was assembly-induced and the electric resonance component disappeared, which is significantly different from that of the spoof LSPs by bulk metal. It was thought and proved by simulation to be relative with the special micro-structure of the gold nanoparticle assemblies. Furthermore, the spoof LSP by gold nanoparticles was flexible and showed a strong relationship between the resonance frequency and the curvature degree of the spoof LSP, meaning that the LSP resonance can be modulated by the deformation of the spoof LSP. We believed that these results could deepen understanding about the spoof LSPs and widen the application in multiple areas. Graphical abstract: Unlabelled Image Highlights: Ultrathin and flexible spoof localized surface plasmon is fabricated by LBL assembly of gold nanoparticles. The spoof localized surface plasmon exhibits assembly-induced LSPR resonance in microwave band. Disappearance of electric resonance component resulting in high surface impedance. Strong relationship between resonance frequency and curvature degree was observed.